Condicionamento do relevo ao longo de zonas de falhas com bandas de deformação na bacia sedimentar Rio do Peixe, Brasil - Barbosa, Ana Beatriz da Silva (2020)
This paper analyzes the importance of fault zones with deformation bands in the resistance to differential weathering of sedimentary rocks, bringing as a case study the Rio do Peixe Basin (RPB), located in northeast of Brazil. The data were obtained using remote sensing, fieldwork, analysis of resistance and topography, extraction of lineaments and development of digital elevation models, topographic profiles and high resolution orthomosaic. We observed that, on a regional scale, there is a heterogeneous distribution of the positive relief features, which are related to the edge fault systems present in the area (Portalegre and Malta faults), and structures deforming the internal structural framework of the basin, being the NE-SW trend predominant both in basement and in RPSB. The topographic profiles showed that there is a correlation between the topographic highs and the occurrence of deformation bands (DBs). DBs are present in the damage zones of the faults that affect the basin, where they present themselves as enclaves of resistance to differential weathering and shape structural ridges. These highest reliefs correspond to the internal portions of the damage zone and, with the decrease in deformation, the primary sedimentary structures are exposed. As it moves away from the fault zone, the topography is lowered and flat, favoring the presence of eluvial covers. This information allowed us to conclude that the relief of the BSRP, in cases close to the fault zones, presents structural conditioning associated with deformational episodes that affected the permeability and resistance of the sandstones, thus leading to the formation of structural ridges.